Kajian Peran Penting Pendidikan Sekolah Advent Dalam Mengembangkan Tabiat dan Karakter Melalui Pratik Pembelajaran Di Sekolah sebagai Wujud Prestasi yang Dicapai - Janes Sinaga; Max Lucky Tinenti; Bernard Maruli Hutabarat; Juita Lusiana Sinambela; Dale Dompas Sompotan (Journal of Education and Culture (JEC), 2022)
After sin entered this world, sin destroyed every system in this world, including the education system. Adventist schools in addition to instilling world knowledge, emphasizes the development of character and character as the government's 2013 Curriculum Education goals and where the goals of character and character development have been carried out for years by Adventist school education everywhere with one goal is to save the spiritual soul by restoring The image and image of God that has been damaged by sin in order to gain eternal life. This study used a qualitative method by processing data from books and journals related to the research material. The purpose of this research is for everyone to understand the purpose and important role of education, especially in Adventist schools which prioritize character education apart from science education. The main goal of Adventist Education is to restore the Image and Image of God in a real form, namely salvation and eternal life someday.